2006
DOI: 10.1207/s15374424jccp3501_11
|View full text |Cite
|
Sign up to set email alerts
|

From CBCL to DSM: A Comparison of Two Methods to Screen for DSM-IV Diagnoses Using CBCL Data

Abstract: The screening efficiency of 2 methods to convert Child Behavior Checklist (CBCL) assessment data into Diagnostic and Statistical Manual of Mental Disorders (4th ed. [DSM-IV]; American Psychiatric Association, 1994) diagnoses was compared. The Machine-Aided Diagnosis (MAD) method converts CBCL input data directly into DSM-IV symptom criteria. The Achenbach System of Empirically Based Assessment (ASEBA) proceeds more indirectly and uses DSM-oriented scales. The power of the 2 methods to predict DSM-IV diagnoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 13 publications
2
38
0
Order By: Relevance
“…Additional analyses revealed that our results were unaffected by controlling for subthreshold oppositional defiant disorder (ODD) symptoms based on the Child Behavior Checklist (CBCL; Krol et al 2006) (Supplementary Tables S1 and S2). In addition, in a supplementary linear model using ADHD as a continuous variable, contrasts revealed that, for all significant associations between ADHD and neurocognitive variables, a linear trend could be detected and no other higher-order link function was statistically significant (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 88%
“…Additional analyses revealed that our results were unaffected by controlling for subthreshold oppositional defiant disorder (ODD) symptoms based on the Child Behavior Checklist (CBCL; Krol et al 2006) (Supplementary Tables S1 and S2). In addition, in a supplementary linear model using ADHD as a continuous variable, contrasts revealed that, for all significant associations between ADHD and neurocognitive variables, a linear trend could be detected and no other higher-order link function was statistically significant (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 88%
“…Similar concerns were voiced by Boots [2008] in her work focusing on the ability of DSMoriented problems to predict serious offending over time in the youngest cohort of Pittsburgh Youth Study boys, as ''it stands to reason that parents may mitigate their child's behaviors because they may view these problems as reflective of their own dysfunction or failure in parenting' ' (p 130-131). With respect to developmentally based research, such as that conducted here, scholars have argued persuasively that the use of multiple informants offers a more comprehensive picture of assessment of functioning across domains and situations than a sole informant can provide [Krol et al, 2006]. Indeed, such designs are ''essential to preserve the contributions of different informants, even if their reports are not correlated highly'' [Renk and Phares, 2004, p 240].…”
Section: Discussionmentioning
confidence: 99%
“…Although the DOSs are not directly equivalent to any clinical diagnosis, they satisfactorily predict DSM-IV diagnoses [30]. Recent twin multivariate genetic epidemiological analyses in the Italian general population showed that compared with the classic CBCL/6-18 empirical subscales, the DOSs have higher heritability (lowest 0.56 and 0.61 for attention deficit/hyperactivity problems and oppositional defiant problems; highest 0.71 for conduct problems), and simpler causal structure, in that the phenotypic variance is satisfactorily explained by additive genetic and unique environmental factors only [48].…”
Section: Behavioural Assessmentmentioning
confidence: 92%